Profil optimisme mahasiswa program studi Bimbingan dan Konseling Universitas Ahmad Dahlan - Aprilia Setyowati; Fadhila Malasari Ardini; Melisa Dewi (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2019)
This study aims to reveal the optimism scale of 2017 Guidance and Counseling Study Program students at the University of Ahmad Dahlan Yogyakarta. This research is a quantitative research with descriptive method. The instrument that uses to get the data is student optimism scale form. The research subjects were 156 students of Ahmad Dahlan University Yogyakarta Guidance and Counseling Study Program. This study used descriptive statistics with percentage techniques for the data analysis. The results showed that 11.54% of students had optimism in the high category, 88.46% of students in the medium category, and 0% of students in the low category. The research results are used by lecturers and university counselors to design programs in order to facilitate students to develop optimism